Archeologiczny przyczynek do dziejów kolegiaty w Łowiczu - Tyszler, Lubomira (Acta Universitatis Lodziensis. Folia Archaeologica, 1994)
Results of archaeological investigations conducted at the collegiate church in Łowicz are discussed. The present church was built in the mid-17th century to the plan of Andrzej Poncino and on the initiative of Maciej Łubieński, archbishop since 1641. The tradition concerning the church goes back to 1100. In 1433 the then parish church, built in timber, was raised to the status of the collegiate church. The erection of the brick church was begun by archbishop Jan of Sprowa (1433-1464). In 1525 the building was destroyed by fire but the extent of the damage is not known. Successive patrons of the collegiate church had various building works done yet for lack of evidence they are hard to assess. In the period from the end of the 16th to the 18th century a number of archbishops’ burial chapels were added. However, either for lack of proper care or because of a number of successive fires the church was not always in a good state of repair. Rescue excavations carried out by the Conservator of Monuments for the Province of Skierniewice in cooperation with the Department of Archaeology of the Łódź University have failed to determine the shape of the building prior to the mid- 17th century. The uncovered remains o f a Gothic wall have only added to our knowledge of the plan of the earliest brick building. Accordingly, it can be assumed that the collegiate church, located on the same site, was a three-aisled construction with an elongated presbytery. The earliest cultural layers, revealed by excavations, date to the mid-14th century whsn an urban centre, granted „town rights” (localio civiias) was being formed. Apart from the churchyard of the 12th—13th centuries, which had already been discovered in the pre-war period and which indirectly indicates the existence of a settlement preceding the locatio and confirms the early date of the church, no other traces of early medieval pre-localio settlement have come to light.